Inflammation as a diagnostic criterion in the GLIM definition of malnutrition—what CRP-threshold relates to reduced food intake in older patients with acute disease? - Pourhassan, Maryam; Cederholm, Tommy; Trampisch, Ulrike; Volkert, Dorothee; Wirth, Rainer (European Journal of Clinical Nutrition, 2021)
Background/objectives: In the recently introduced GLIM diagnosis of malnutrition (Global Leadership Initiative on Malnutrition), details of how to classify inflammation as an etiologic criterion are lacking. This study aimed to determine at what level of serum C-reactive protein (CRP) the risk of low food intake increases in acutely ill older hospitalized patients. Subjects/methods: A total of 377 patients, who were consecutively admitted to a geriatric acute care ward, were analyzed. Nutritional intake was determined using the food intake item of Nutritional Risk Screening and the plate diagram method and patients were grouped into three categories as >75%, 50–75% and ≤50% of requirements. CRP was analyzed according to standard procedures and patients were classified into different CRP groups as follows: 0.0–0.99 mg/dl, 1.0–1.99 mg/dl, 2.0–2.99 mg/dl, 3.0–4.99 mg/dl, 5.0–9.99 mg/dl and ≥10.0 mg/dl. Results: Of the total population (mean age of 82.2 ± 6.6 years; 241 females), 82 (22%) had intake <50% of requirements and 126 (33%) demonstrated moderate to severe inflammation. Patients with food intake <50% of requirements had a significantly higher median CRP level compared to patients with food intake >75% of requirements (P < 0.001). The group with serum-CRP levels above 3.0 mg/dl had a markedly higher proportion of patients with low food intake; i.e., <50% and <75% of the requirements. Conclusion: A serum-CRP of 3.0 mg/dl appears to be a reasonable threshold of acute inflammation leading to reduced food intake to serve as an orientation with regard to the inflammation criterion of the GLIM diagnosis in acutely ill older patients.
CRIS-Team Scopus Importer:2021-07-30